Effects of emulating the presence of virtual confederates on social conformity - dos Santos, Vinícius S. G.; Moreira, Márcio Borges; Barbieri, Daniel; Cavalcanti, Paulo (Perspectivas em Análise do Comportamento, 2022)
The aim of this research was to investigate the effect of virtual confederates' choices on participants' choices in an online vertical line size comparison task (social compliance). Additionally, it was verified whether the composition of the confederates group, in terms of the gender of the confederates, could influence the participants' choices. Five university students participated in the survey. An online software emulated the presence of confederates in the task, presented the attempts and recorded the participants' responses. The experimental task consisted of looking at a line on the computer screen and then choosing from three lines which was the same size as the model line. Before the participant responded, he had access to the virtual confederate choices. In general, the occurrence of compliance was verified for all participants. Regarding the secondary objective of the research, the results suggest that the composition of the group of confederates, in terms of their gender, was not sufficient to establish discriminative control over the behavior of the participants. The results were discussed in terms of experimental control problems derived from an online collection and emulation of the participation of others in the experimental task.